Temperature and wind velocity effects on bit error rate during free space optical link under Matrix Málaga turbulence channel - Mbezi, M Teuma; Samuel, Eke; Som, H J Idelette; Mouangue, R M (Sadhana (Bangalore), 2023)
FSO transmission is disturbed by atmospheric turbulence due to thermal and wind dynamic instability. The aim of this work is to study the coupled effects of temperature and wind velocity on the BER using Matrix Málaga atmospheric turbulence channel model (ℳ. ℳ). To achieve this purposes, average BER expression was established using ℳ. ℳ. Then considering Monin-Obukhov similarity functions for the structure parameters of temperature, relationships were established between both the amount of fading parameter, the effective number of large-scale cells, with temperature and wind velocity. The study shows that there are non-linear effects of temperature and wind velocity on BER. Under dynamic turbulence, one can appropriately modify temperature to reduce BER due to dynamic instability and reciprocally. M-QAM modulation scheme seems to be more robust to support turbulent effect since its increased regions size of low BER. Using variable antenna height during FSO installation lead to reduce BER due to specific atmospheric turbulence.